Pengaruh Whistleblowing System, Proteksi Awig-Awig dan Implementasi Good Corporate Governance Terhadap Kecenderungan Kecurangan (Fraud) - I Putu Edi Saputra; Ni Wayan Yuniasih; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2023)
The aim of this study was to assess the impact of the whistleblowing system, awig-awig protection, and good corporate governance on the likelihood of fraud in LPDs across the Kerambitan Area. The study was conducted among 27 LPDs and 136 LPD employees in the Kerambitan District, using a saturated sample method for participant selection and a questionnaire for data collection. Multiple linear regression analysis was performed on the data collected. The findings indicate that (1) the whistleblowing system has a significant and negative impact on fraud tendencies, (2) awig-awig protection does not have a significant impact on fraud tendencies, and (3) the implementation of good corporate governance has a significant and negative impact on fraud tendencies